The role of Sn on the long-term atmospheric corrosion of binary Cu-Sn bronze alloys in architecture. (1st April 2019) - Chang, T.; Herting, G.; Goidanich, S.; Sánchez Amaya, J.M.; Arenas, M.A.; Le Bozec, N.; Jin, Y.; Leygraf, C.; Odnevall Wallinder, I.
Graphical abstract: Highlights: Long-term atmospheric corrosion and metal release studies of Sn-bronze and Cu metal at urban and marine environments. The presence of Sn oxides in the native Cu2 O rich surface oxide of Sn-bronze improves its barrier properties. Sn alloying reduces the corrosion rate of Sn bronze at urban conditions. No beneficial corrosion effects of Sn alloying at chloride-rich marine conditions. Metal release marginally influenced by Sn alloying. Abstract: The role of Sn on the atmospheric corrosion performance of binary Cu-Sn bronze alloys (4–6 wt.% Sn) compared with Cu metal used in outdoor architecture is elucidated in terms of microstructure, native surface oxide composition, patina evolution, corrosion rates, appearance and metal release. Results are presented for non-exposed surfaces and surfaces exposed at different urban and marine sites in Europe up to 5 years and based on multi-analytical findings from microscopic, spectroscopic, electrochemical and chemical investigations. Alloying influenced the corrosion, aesthetic appearance and patina evolution, differently for urban and marine sites, whereas no effects were observed on the release pattern.